2006
DOI: 10.1074/jbc.m511767200
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That DNA (Cytosine-5) Methyltransferase Regulates Synaptic Plasticity in the Hippocampus

Abstract: DNA (cytosine-5) methylation represents one of the most widely used mechanisms of enduring cellular memory. Stable patterns of DNA methylation are established during development, resulting in creation of persisting cellular phenotypes. There is growing evidence that the nervous system has co-opted a number of cellular mechanisms used during development to subserve the formation of long term memory. In this study, we examined the role DNA (cytosine-5) methyltransferase (DNMT) activity might play in regulating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
449
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 572 publications
(481 citation statements)
references
References 61 publications
19
449
1
6
Order By: Relevance
“…One line of evidence comes from studies of epigenetic changes during long-term potentiation and fear conditioning by Sweat's group [Levenson et al, 2006;Miller and Sweatt, 2007] and the other line of evidence is our study of epigenetic programming by maternal care .…”
Section: How Could Behavior Modulate Dna Methylation? the Dynamic Patmentioning
confidence: 99%
See 1 more Smart Citation
“…One line of evidence comes from studies of epigenetic changes during long-term potentiation and fear conditioning by Sweat's group [Levenson et al, 2006;Miller and Sweatt, 2007] and the other line of evidence is our study of epigenetic programming by maternal care .…”
Section: How Could Behavior Modulate Dna Methylation? the Dynamic Patmentioning
confidence: 99%
“…In the first set of experiments they have shown that treatment of nondividing neurons in hippocampal slices in culture with a protein kinase c activator phorbol-12,13-diacetate results in rapid increase in histone acetylation and demethylation of the reelin gene, a gene implicated in synaptic plasticity and learning [Levenson et al, 2006]. This is evidence that active demethylation activity is present in postmitotic neurons.…”
Section: Evidence That the Dynamic Dna Methylation Pattern Participatmentioning
confidence: 99%
“…These covalent modifications of DNA and histone proteins regulate the degree of compaction or relaxation of chromatin, and permit or restrict access of regulatory molecules to DNA. Biological processes related to epigenetics include gene transcriptional regulation, imprinting, X-chromosome inactivation, pluripotency, differentiation, noncoding RNA function, and synaptic plasticity [20,22]. DNA methylation, the topic of this review, is the major direct modification of eukaryotic DNA and is known to have profound effects on the regulation of gene expression [20,[23][24][25].…”
Section: Dna Methylation As An Epigenetic Mechanismmentioning
confidence: 99%
“…Our discovery that Dnmt3a, but not Dnmt1, is located in presynaptic axon terminals in the adult CNS is exciting because it identifies a local presynaptic possibility for Dnmt3a in regulating synaptic function. Studies have shown that Dnmts function in synaptic plasticity [22,71] and behavioral plasticity [72]. Mice with conditional knockout of Dnmt1 and Dnmt3a, and with hypomethylation in forebrain show deficits in learning and memory distinct from single knockout mice, which show similar changes on behavioral tasks, suggesting that Dnmt1 and Dnmt3a have some overlapping functions in neurons [73].…”
Section: Mammalian Dnmts In the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation